Medical work or counselling work?: a qualitative study of genetic counselling - Pearce, Melanie D. (2004)
This thesis presents a qualitative study of genetic counselling. Using a combination of semi-structured interviews and conversation analysis, it focuses on the role, function and structure of genetic counselling and on its status as medical or counselling work. Semi-structured interviews are used to ascertain genetic counsellors' accounts or perceptions of the nature of their role, their views on client expectations, and genetic counselling clients' perceptions and expectations of the same. Conversation analytic study of recorded genetic counselling consultations is used to identify whether or not they possess an overall shape and whether they appear conversationally as a counselling or a medical interaction. Rose's (1998, 1999) sociological work on the growth of the therapeutic community and the techne of 'psy' provides a framework for a discussion on the strength of the genetic counselling profession's association with a Rogerian counselling philosophy and on the potential difficulties this may bring. The questions are raised; does genetic counselling have many similarities to "personal, emotional or psychological" 'counselling' at all? And is this alliance with the counselling community either fair or possible for the professionals involved? The results were as follows. First, that the genetic counselling consultations in this corpus do not present with one unique overall shape that can encompass all interactions. Second, that the accounts of the genetic counsellors and clients in this sample, and the conversation analytic study of the recorded consultations, suggest that genetic counselling is primarily a medical-based activity and that this is what clients want. Third, that genetic counselling has a number of dissimilarities to psychotherapeutic counselling that suggest it is not so much 'counselling' as using counselling skills, and finally, that the tensions incurred in fulfilling medical-type tasks within what is ostensibly a 'counselling' role are neither fair nor practical for the professionals involved.